The Politics of Preservation and Loss: Tibetan Medical Knowledge in Exile. Issue 2 (1st June 2017) - Kloos, Stephan
Abstract : This article analyzes the history and development of Tibetan medicine in exile from the perspective of the pervasive Tibetan exile narrative of preservation and loss. Through combined ethnographic and historical data, it shows how the preservation of traditional Tibetan medical knowledge in exile entails a process of a fundamental reinvention of its nature, not only rendering it modern but also (re)investing it with considerable hegemonic power. As Tibetan medicine in exile has come to stand for the nation as envisioned by the Tibetan government-in-exile, its preservation is imbued with a significance that far exceeds the medical realm. Indeed, despite a well-established discourse of preservation and loss that implies a precarious state of weakness, Tibetan medical knowledge functions (along with Tibetan Buddhism) as an important means to preserve a weakened but still existing and real Tibetan cultural hegemony in exile. Thus, while common rhetoric assumes a triumph of modern science and a gradual loss of traditional knowledge, the case of Tibetan medicine shows that we need to take the latter seriously as an important apparatus of power even today.